SISTEM PAKAR UNTUK MENGANALISA GANGGUAN DI JARINGAN TEGANGAN RENDAH BERBASIS KASUS - Titi Ratnasari (Energi & Kelistrikan, 2015)
PLN is the only company in Indonesia that serves and supplies electricity which is a necessity for many people. Various PLN’s customer needs electricity to do all of their activities. However ifthere is an interference in the electricity distribution, then all of the activities will stop. That results the decrease of PLN’s quality of service and must be increased by handling all of the interference as quickly as possible. One of the tools to solve electricity interference quickly and accurately is by developing an expert system. In this research, an expert system was developed to help identifyingelectricity interference quickly and accurately from customer’s reports. Case based reasoning is the method that is used in developing the expert system in this research and backward chaining is the inference machine. Based on the results of the verification and validation of PLN’s expert, interference unit operator, and field technician; showed that the system was able to identify theinterference that occurred and gave an accurate solution toward customer’s report.